Paediatric spinal surgery and perioperative management - Yrjälä, Tommi (fi=Turun yliopisto|en=University of Turku|, 2023)
The aim of this dissertation is to improve perioperative management of adolescent patients undergoing posterior spinal fusion surgery. Posterior spinal fusion surgery is one of the most common major surgical procedures in adolescents. It is the main surgical procedure performed in adolescents with adolescent idiopathic scoliosis, Scheuermann kyphosis, or spondylolisthesis. The first part of this thesis was a randomised, double-blinded, and placebo-controlled clinical trial of 64 patients. The purpose of the first study was to determine whether perioperative pregabalin reduces the persistent pain in adolescent patients after posterior spinal fusion for spinal deformities compared to placebo. The second and third part of this thesis were retrospective analyses of a prospectively collected paediatric spine register. In the second study, 159 consecutive adolescent idiopathic scoliosis patients undergoing posterior spinal fusion were screened to determine the predictors of postoperative urinary retention. The third part of this thesis included 158 adolescent idiopathic scoliosis, 19 Scheuermann kyphosis, and 36 spondylolisthesis patients undergoing posterior spinal fusion surgery, with the aim of evaluating the predictors of acute and chronic pain. In our first study, we showed that pregabalin did not affect the chronic postoperative pain two years after surgery, and there is no reason to combine pregabalin to a multimodal treatment protocol in adolescents undergoing posterior spinal fusion. In our second study, we revealed that postoperative opioid consumption after posterior spinal fusion was associated with an increased risk of postoperative urinary retention in adolescent idiopathic scoliosis patients, and multimodal pain management to reduce the opioid amount may be beneficial. The third publication of this thesis demonstrated that after posterior spinal fusion, acute postoperative pain was associated with more extensive tissue trauma (adolescent idiopathic scoliosis and Scheuermann kyphosis), and chronic pain was related to the disease pathology (spondylolisthesis). Multimodal analgesia may reduce the persistent pain, but an optimal treatment protocol is still not established, and more studies are needed.

Lasten selkäleikkausten perioperatiivinen hoito Tämän väitöskirjan tavoitteena on parantaa nuorten selän luudutusleikkaus potilaiden perioperatiivista hoitoa. Selän luudutusleikkaus on yksi yleisimpiä laajaa kirurgiaa vaativista toimenpiteistä nuorilla. Se on yleisin kirurginen toimenpide, joka tehdään nuorille, joilla on idiopaattinen skolioosi, Scheuermannin kyfoosi tai spondylolisteesi. Suomessa tehdään vuosittain n. 250 selän luudutusleikkausta nuorille. Tämän väitöskirjan ensimmäinen osatutkimus oli satunnaistettu, kaksoissokkoutettu ja lumekontrolloitu kliininen tutkimus 64 potilaalla. Ensimmäisen tutkimuksen tarkoituksena oli selvittää, vähentääkö perioperatiivinen pregabaliini kroonista kipua nuorilla selän luudutusleikkauksen jälkeen verrattuna lumelääkkeeseen. Toinen ja kolmas tutkimus olivat retrospektiivisiä analyysejä prospektiivisesti kerätystä lasten selkärekisteristä. Toisessa tutkimuksessa tarkastettiin rekisteristä 159 peräkkäisen selkäluudutetun nuoren idiopaattisen skolioosipotilaan tiedot. Tarkoituksena oli löytää virtsaummen esiintyvyys ja riskitekijät. Kolmannessa tutkimuksessa oli 158 nuorta idiopaattista skolioosi-, 19 Scheuermannin kyfoosi- ja 36 spondylolisteesipotilasta, joille oli tehty selän luudutusleikkaus. Tavoitteenamme oli selvittää, miten eri sairaudet vaikuttavat leikkauksen jälkeiseen akuuttiin ja krooniseen kipuun. Ensimmäisessä tutkimuksessamme osoitimme, että pregabaliini ei vaikuttanut krooniseen leikkauksen jälkeiseen kipuun kaksi vuotta luudutusleikkauksen jälkeen, eikä ole mitään syytä yhdistää pregabaliinia multimodaaliseen hoitokäytäntöön nuorille selän luudutusleikkauksen jälkeen. Toisessa tutkimuksessamme osoitimme, että nuorilla idiopaattista skolioosia sairastavilla luudutusleikkauksen jälkeinen opioidien kulutus korreloi virtsaummen esiintyvyyden kanssa. Multimodaalisella kivunhoidolla saatetaan vähentää virtsaummen riskiä. Kolmannessa julkaisussa osoitimme, että selän luudutusleikkauksen jälkeinen akuutti kipu liittyi laajempaan kudostraumaan (nuorten idiopaattinen skolioosi ja Scheuermannin kyfoosi), ja krooninen kipu liittyi sairauden patologiaan (spondylolisteesi). Multimodaalinen kivunhoito vähentää akuuttia ja voi vähentää kroonista kipua, mutta optimaalista hoitokäytäntöä ei ole vielä löydetty, ja lisää tutkimuksia tarvitaan.